Burkholderia Cepacia: An Emerging Superbug in Intensive Care Unit Settings of Tertiary Care Hospitals in Pakistan - Rafia Irfan; Amna Amer; Irfan Ali Mirza; Wajid Hussain; Mariam Sarwar; Mahtab Akhtar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency, risk factors, and antibiotic susceptibility pattern of Burkholderia cepacia isolates from clinical specimens in a Pakistani tertiary care hospital.